Characterization of N6-Cyclohexyladenosine-Induced Hypothermia in Syrian Hamsters - Mitsuteru Shintani; Yutaka Tamura; Mayuko Monden; Hirohito Shiomi (Elsevier, 2005)
The N6-cyclohexyladenosine (CHA)-induced hypothermia in Syrian hamsters was characterized as follows: intracerebroventricular injection of CHA-induced hypothermia and the potency was increased by lowering the ambient temperature. CHA microinjection into the anterior hypothalamus (AH) elicited the most marked body temperature (Tb) decrease compared with other regions such as the preoptic area, dorsomedial hypothalamus, posterior hypothalamus, and hippocampus. In contrast, microinjected CHA into the medial septum, ventromedial hypothalamus, and lateral hypothalamus resulted in negligible changes in Tb. These results suggest that CHA-induced hypothermia was probably due to suppression of thermogenesis via the site(s) of CHA action, viz., the AH and medial hypothalamus. Keywords:: adenosine, hypothermia, anterior hypothalamus